Shannon entropy: A novel parameter for quantifying pentagon copying performance in non-demented Parkinson's disease patients - Brabenec, Lubos; Klobusiakova, Patricia; Mekyska, Jiri; Rektorova, Irena (Parkinsonism & related disorders, 2022)
INTRODUCTION: Impaired copy of intersecting pentagons from the Mini-Mental State Examination (MMSE), has been used to assess dementia in Parkinson's disease (PD). We used a digitizing tablet during the pentagon copying test (PCT) as a potential tool for evaluating early cognitive deficits in PD without major cognitive impairment. We also aimed to uncover the neural correlates of the identified parameters using whole-brain magnetic resonance imaging (MRI). METHODS: We enrolled 27 patients with PD without major cognitive impairment and 25 age-matched healthy controls (HC). We focused on drawing parameters using a digitizing tablet. Parameters with between-group differences were correlated with cognitive outcomes and were used as covariates in the whole-brain voxel-wise analysis using voxel-based morphometry; familywise error (FWE) threshold p < 0.001. RESULTS: PD patients differed from HC in attention domain z-scores (p < 0.0001). In terms of tablet parameters, the groups differed in Shannon entropy (horizontal in-air, p = 0.003), which quantifies the movements between two strokes. In PD, a correlation was found between the median of Shannon entropy (horizontal in-air) and attention z-scores (R = -0.55, p = 0.006). The VBM revealed an association between our drawing parameter of interest and gray matter (GM) volume variability in the right superior parietal lobe (SPL). CONCLUSION: Using a digitizing tablet during the PCT, we identified a novel entropy-based parameter that differed between the nondemented PD and HC groups. This in-air parameter correlated with the level of attention and was linked to GM volume variability of the region engaged in spatial attention.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; neuropsychologické testy; Entropy; In-air movement; Kinematic analysis; lidé; Parkinson's disease; Gray Matter; Neuropsychological Tests; Cognitive Dysfunction; šedá hmota; Pentagon copying test; Shannon entropy; Parkinson Disease; kognitivní dysfunkce; entropie; Parkinsonova nemoc